Cervical Arthroplasty: Long-Term Outcomes of FDA IDE Trials. Issue 2 (April 2020) - Parish, Jonathan M.; Coric, Domagoj
Study Design: Special Issues MIS/Navigation. Objectives: Over the past decade, cervical total disc replacement has been established in numerous randomized clinical trials as an alternative to anterior cervical discectomy and fusion. The purpose of this review is to evaluate the long-term outcomes after cervical arthroplasty. Methods/Results: Early outcomes (studies with 2-year follow-up) after arthroplasty established the efficacy of total disc replacement and, more recently, long-term studies have shown the durability of these good clinical outcomes. Biomechanical and clinical data have demonstrated that this motion preservation technology decreases adjacent-level stresses compared with fusion. Additionally, long-term outcomes as well as outcomes after multilevel arthroplasty have now established the role of arthroplasty in select patient populations, namely patients with 1- and 2-level spondylosis/stenosis causing radiculopathy from C3-7. Conclusions: Data on adjacent segment deterioration and adjacent segment reoperation remains controversial but suggest a positive effect after arthroplasty. But these are multifactorial issues and we still do not fully understand all the factors affecting adjacent segment pathology and longer-term studies after arthroplasty will continue to address this issue.